2023
DOI: 10.1021/acs.jafc.3c00611
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Polysaccharides of Aspergillus cristatus from Fuzhuan Brick Tea Leverage the Gut Microbiota and Repair the Intestinal Barrier to Ameliorate DSS-Induced Colitis in Mice

Abstract: The intracellular polysaccharides of Aspergillus cristatus (IPSs) from Fuzhuan brick tea have been demonstrated to improve immune function linked to modulating the gut microbiota. Herein, to further investigate the efficacy of IPSs to maintain gut homeostasis, the protection of the purified fraction of IPSs (IPSs-2) on the mice with colitis induced by dextran sulfate sodium (DSS) and the underlying mechanisms were explored in this study. The results revealed that IPSs-2 alleviated the typical symptoms of colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The profound changes in gut taxa, metabolites, and inflammatory markers provided a detailed insight into the therapeutic mechanism of HLL in UC. Xie et al [ 52 ] reported that the intracellular polysaccharides in Aspergillus cristatus from Fuzhuan brick tea can alleviate symptoms of DSS-induced colitis in mice by repairing the intestinal barrier. And Lu et al [ 53 ] noted that the polysaccharides in Eurotium cristatum from Fuzhuan brick tea can ameliorate colitis in mice by modulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The profound changes in gut taxa, metabolites, and inflammatory markers provided a detailed insight into the therapeutic mechanism of HLL in UC. Xie et al [ 52 ] reported that the intracellular polysaccharides in Aspergillus cristatus from Fuzhuan brick tea can alleviate symptoms of DSS-induced colitis in mice by repairing the intestinal barrier. And Lu et al [ 53 ] noted that the polysaccharides in Eurotium cristatum from Fuzhuan brick tea can ameliorate colitis in mice by modulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For immunofluorescence staining, the tissue slices were incubated with primary antibodies (F4/80, CD11c, CD206, GLP-1, ZO-1, and Occludin) overnight at 4 °C after deparaffinization, rehydration, and antigen retrieval and sealing. Then, they were stained with secondary antibodies with Alexa Fluor Plus 488 or Alexa Fluor 594 fluorescently labeled goat antirabbit IgG according to the method reported in literature . For the statistical analysis of the morphological structure of intestinal segments, the percentages of F4/80, CD11c, CD206, GLP-1, ZO-1, and the Occludin immunostaining positive area were counted as the abovementioned method.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Then, they were stained with secondary antibodies with Alexa Fluor Plus 488 or Alexa Fluor 594 fluorescently labeled goat antirabbit IgG according to the method reported in literature. 19 For the statistical analysis of the morphological structure of intestinal segments, the percentages of F4/80, CD11c, CD206, GLP-1, ZO-1, and the Occludin immunostaining positive area were counted as the abovementioned method. All images were photographed on a confocal laser-scanning microscope (FV1000, Olympus, Tokyo, Japan).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The catechins act in a dual modality, stimulating healthy gut microbes and inhibiting the proliferation of Campylobacter jejuni, Bacillus cereus, Escherichia coli, Clostridium perfringens, Legionella pneumophila, and Helicobacter pylori through a disruption of the cell membrane. Furthermore, green-tea polyphenols are able to create an overproliferation of Faecalibacterium, Bifidobacterium, Eubacterium, and Roseburia that lead to an increase in SCFAs with proven effects against colorectal cancer because they suppress lipopolysaccharide synthesis and, consequently, potentiate immune system function and exert an anti-inflammatory action [76][77][78][79][80][81][82]. Citrus fruits, like Citrus reticulate, or mandarin oranges; Citrus sinesis, or sweet oranges; Citrus depressa, or flat lemons; Citrus aurantium, or bitter oranges; and, especially, Citrus tangerine, or tangerines, contain nobiletin, a flavone with a chemical structure of three aromatic rings, each one linked to specific molecular groups.…”
Section: Colon Cancermentioning
confidence: 99%
“…Experiments in a mouse model about an estrogen-receptor (ER) negative mammary tumor showed that polyphenols alone did not induce a significative change in the gut-microbiota composition of healthy mice, even if they reduced significantly the rate of Firmicutes communities; in contrast, after cancer onset, these natural compounds effectively modified gut microbes, leading to a reduction of Proteobacteria and an increase in Bacterioides, compared to the control group. Furthermore, these changes are more evident after a combined administration of both broccoli sprouts and green-tea polyphenols [76][77][78][79][80][81]. Other plants and vegetables have shown antioxidant and anticancer properties.…”
Section: Breast Cancermentioning
confidence: 99%